Energy intake and expenditure assessed `in-season` in an elite European rugby union squad - Bradley, W. J.; Cavanagh, B.; Douglas, W.; Donovan, T. F.; Twist, C.; Morton, J. P.; Close, G. L. (European Journal of Sport Science, 2015)
Rugby union (RU) is a complex high-intensity intermittent collision sport with emphasis placed on players possessing high lean body mass and low body fat. After an 8 to 12-week pre-season focused on physiological adaptations, emphasis shifts towards competitive performance. However, there are no objective data on the physiological demands or energy intake (EI) and energy expenditure (EE) for elite players during this period. Accordingly, in-season training load using global positioning system and session rating of perceived exertion (sRPE), alongside six-day assessments of EE and EI were measured in 44 elite RU players. Mean weekly distance covered was 7827 ± 954 m and 9572 ± 1233 m with a total mean weekly sRPE of 1776 ± 355 and 1523 ± 434 AU for forwards and backs, respectively. Mean weekly EI was 16.6 ± 1.5 and 14.2 ± 1.2 megajoules (MJ) and EE was 15.9 ± 0.5 and 14 ± 0.5 MJ. Mean carbohydrate (CHO) intake was 3.5 ± 0.8 and 3.4 ± 0.7 g.kg-1 body mass, protein intake was 2.7 ± 0.3 and 2.7 ± 0.5 g.kg-1 body mass, and fat intake was 1.4 ± 0.2 and 1.4 ± 0.3 g.kg-1 body mass. All players who completed the food diary self-selected a `low` CHO `high` protein diet during the early part of the week, with CHO intake increasing in the days leading up to a match, resulting in the mean EI matching EE. Based on EE and training load data, the EI and composition seems appropriate, although further research is required to evaluate if this diet is optimal for match day performance